Two new species of Allonychiurus Yoshii, 1995 (Collembola, Onychiuridae) from eastern China, with a key to world species of the genus - Chang, Liang; Sun, Xin (Zootaxa, 2016)
Two new species, Allonychiurus zhejiangensis sp. nov. and Allonychiurus pseudokimi sp. nov., have been reported from eastern China. A. zhejiangensis sp. nov. is particular in the genus as having three pso on ventral side of the head. A. pseudokimi sp. nov. is similar to A. kimi, but they can be distinguished by the number of pso on ventral side of the head, the number of chaetae along axial line on Abd. I–II, the number of chaetae on ventral tube and the presence of basal lamella on unguiculus. A key to the known species of the genus all over the world is given accordingly.